Understanding legitimacy: Perspectives from anomalous geopolitical spaces. (November 2015) - Jeffrey, Alex; McConnell, Fiona; Wilson, Alice
Highlights: Explores political legitimacy from the angle of anomalous geopolitical spaces. Examines the centrality of legitimacy for the enactment of political authority. Highlights the interdisciplinary significance of legitimacy. Investigates anomalous geopolitical spaces as a window onto legitimacy. Abstract: This special issue explores the production of political legitimacy, approached from the angle of the legitimacy claims of the governing authorities of anomalous geopolitical spaces. Legitimacy sits at the heart of theories of sovereign power, a position that has drawn a range of scholars – be they political geographers, political anthropologists, international lawyers or political scientists – to focus on the state as a primary source of political legitimacy. This special issue starts from a different premise: namely, that by studying alternative sites of legitimacy, so-called de facto states, annexed territories, governments-in-exile, liberation movements or unrecognised governments, we may shine a light on the wider arena of political actors, forms of agency and sites of contestation through which legitimacy is produced. This special issue introduction draws attention to, first, the centrality of questions of legitimacy to the enactment of political authority; second, the plural disciplinary and political interpretations of legitimacy, staking a claim for why this study has interdisciplinary significance; and, third, the spatial and temporal importance of studying anomalous geopolitical spaces. The latter are presented as zones that have often been neglected areas of comparative study but may hold the key to understanding the complexities of political legitimacy in the modern world. The introduction concludes with an overview of the themes contained within the individual papers that comprise this special issue.